KIMBERLITES AND RELATED ROCKS OF THE ARKHANGEL'SK DIAMONDIFEROUS PROVINCE AND ADJACENT AREAS: A COMPARATIVE PETROGEOCHEMICAL ANALYSIS - Lapin A.V.; Verichev E.M. (My University, 2006)
The formational and metallogenic affiliation of the alkaline ultramafic rocks of the Arkhangel'sk diamondiferous province and the adjacent areas of the northern East European platform were analyzed using recent concepts on the structure of the formational and metallogenic family of kimberlites and related rocks, petrogeochemical criteria, and discriminant diagrams based on reference associations. It was shown that the alkaline ultramafic magmatism of the Arkhangel'sk province belongs to various formations, which is typical of the provinces of ancient craton margins. In addition to diamondiferous kimberlites, the area hosts abundant low-grade diamondiferous kimpicrites and alpicrites, which are typically associated with rare-metal carbonatites. Significant petrogeochemical differences were detected between the diamondiferous kimberlites of the Arkhangel'sk province and the kimberlites of the lassic Central Yakutian diamondiferous province. This allowed us to consider the rocks of the Arkhangel'sk province as a specific geochemical type of diamondiferous kimberlites. © Pleiades Publishing, Inc. 2006.